Administrative convergence in the United Nations system? Patterns of administrative reform in four United Nations organizations over time. (December 2021) - Grohs, Stephan; Rasch, Daniel
This article asks how and why United Nations organizations reform their administrative structure and processes over time. It explores whether we can observe a convergence towards a coherent administrative model in the United Nations system. Like in most nation states, reform discussions according to models like New Public Management or post-New Public Management have permeated international public administrations. Against this background, the question of administrative convergence discussed for national administrative systems also arises for United Nations international public administrations. On the one hand, similar challenges, common reform 'fashions' and an increasing exchange within the United Nations system make convergence likely. Yet, on the other hand, distinct tasks, administrative styles and path dependencies might support divergent reform trajectories. This question of convergence is addressed by measuring the frequency, direction and rationales for reforms, using a sample of four international public administrations from the United Nations' specialized agencies (the Food and Agriculture Organization, International Labour Organization, International Monetary Fund and World Bank). We find that convergence depends on the area of reform (human resources or organizational matters are more harmonized than others) and time (some international public administrations are faster or earlier than others). Points for practitioners: This article identifies different drivers of reforms, as well as several supporting conditions, and obstacles to reform in international public administration, which is useful for understanding and planning change management. It highlights the issues policymakers should consider when implementing reform measures, especially institutional context, administrative styles and relevant actor constellations. Among other things, it shows that: the establishment of coordination bodies clearly leads to more homogeneous administrative practices; executive heads have a decisive role in the shaping of administrative reforms and have a specific interest to foster coordination and control in public organizations; and autonomy enables organizations to pursue reform policies apt to their individual challenges.